2012
DOI: 10.1016/s1514-0326(12)60010-5
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment Hysteresis: Empirical Evidence for Latin America

Abstract: This paper analyzes the unemployment dynamics of 18 Latin American countries for the last four decades. We use a time series approach to test the mean reversion of unemployment rates and its approximation to a Natural Rate of Unemployment (NRU). The tests include the possibility of one and two structural changes to account for the occurrence of significant macroeconomic changes experienced by the Latin American economies. In addition, we estimate the order of integration of the series, allowing for fractional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…There should be a sufficient period of time to reestablish the equilibrium 8 (Akay et al, 2011, p. 490). Ayala et al (2012) also note that the unemployment rate has a constant long memory process according to the persistence view. This is also supported by the arguments of Mitchell (1993), in which the effects of the shocks on unemployment are assumed as having long durations.…”
Section: Hysteresis In Unemployment: Theoretical Underpinningsmentioning
confidence: 99%
“…There should be a sufficient period of time to reestablish the equilibrium 8 (Akay et al, 2011, p. 490). Ayala et al (2012) also note that the unemployment rate has a constant long memory process according to the persistence view. This is also supported by the arguments of Mitchell (1993), in which the effects of the shocks on unemployment are assumed as having long durations.…”
Section: Hysteresis In Unemployment: Theoretical Underpinningsmentioning
confidence: 99%
“…The study of Blanchard and Summers (1986) is at the forefront of the empirical studies on unemployment hysteresis. Apart from this study, other examined empirical studies are as follows: Brunello (1990), Neudorfer et al (1990), Jaeger and Parkinson (1994), Røed (1996), Song and Wu (1997), Arestis and Mariscal (1999), Papell et al (2000), León-Ledesma (2002), Camarero and Tamarit (2004), Camarero et al (2006), Gustavsson and Österholm (2006), Camarero et al (2008), Gomes and Da Silva (2008), Lee and Chang (2008), Lee et al (2009), Lee (2010), Chang (2011), Ayala et al (2012), Cevik and Dibooglu (2013), Lee et al (2013), Bakas and Papapetrou (2014), Cheng et al (2014), Furuoka (2014), Tiwari (2014), Jiang and Chang (2016), Akdoğan (2017), Güriş et al (2017), Meng et al (2017), Bahmani-Oskooee et al (2018), Rodriguez-Gil (2018), Yaya et al (2019), Khraief et al (2020), Omay et al (2020), Yilanci et al (2020), Omay et al (2021), Bostancı and Koç (2022), Caporale et al (2022),…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bahmani-Oskooee, Chang, and Ranjbar (2017) focused on the United States and found partial evidence of hysteresis through stochastic dynamics of the unemployment rate. Ayala, Cuñado, and Gil-Alana (2012) examined eighteen Latin American countries, including Colombia, and concluded that sixteen of them exhibited evidence of hysteresis based on unit root tests and parametric models, considering endogenous structural changes.…”
Section: Literature Reviewmentioning
confidence: 99%